2019
DOI: 10.3390/economies8010001
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rainfall on Economic Growth in Thailand: A Blessing for Poor Provinces

Abstract: Rainfall is related to economic growth and generally has beneficial impacts on dry and poor areas that are mostly dependent on rainfed agriculture. Thailand is a service-based, upper middle-income country with a tropical climate although rainfall varies regionally. The volume of precipitation in the northern and northeastern regions is rather low while the southern region has the highest rainfall due to its narrow topography running north-south bordering the Andaman Sea to the west and the Gulf of Thailand to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…According to World Bank [83], the contribution of agriculture, forestry, and fishing to Saudi Arabia's GDP was 2.23% in 2019. The negative impact of rainfall on economic growth is also substantiated by Sangkhaphan and Shu [60] who found rainfall in the case of Thailand negatively impacted on agriculture and service sectors, subsequently reducing economic growth. Higher rainfall is presumably conducive for economic growth, specifically in drought-prone countries.…”
Section: Plos Onementioning
confidence: 87%
See 1 more Smart Citation
“…According to World Bank [83], the contribution of agriculture, forestry, and fishing to Saudi Arabia's GDP was 2.23% in 2019. The negative impact of rainfall on economic growth is also substantiated by Sangkhaphan and Shu [60] who found rainfall in the case of Thailand negatively impacted on agriculture and service sectors, subsequently reducing economic growth. Higher rainfall is presumably conducive for economic growth, specifically in drought-prone countries.…”
Section: Plos Onementioning
confidence: 87%
“…Some studies have assessed the effects of rainfall fluctuation on sectoral and economic growth by using different analytical models. For example, Sangkhaphan and Shu [ 60 ] recently stated that rainfall has reduced growth at the national level through its significant negative effect on agriculture and service sectors, but helped the economies of poor parts of the world, which contradicts the results of Solaun and Cerdá [ 61 ]. Ayinde et al [ 62 ] has revealed in their study that an increase in rainfall has a positive effect on economic growth, which has been supported by Miguel et al [ 63 ], Ali [ 53 ], Cabral [ 64 ], and Odusola and Abidoye [ 2 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there is little literature and empirical evidence for the short term, associated with Pandemic-type catastrophes such as COVID-19 with its daily dynamics. However, there are studies where epidemiological [26], climatic factors: rainfall [27,28], temperature [29][30][31] and environmental [32,33] are recognized, which emphasize the impact of economic activity. According to the SIR model, it has proven to be a good indicator of the evolution of COVID-19 [34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is hypothetically assumed that there is an inverse causal relationship between temperature and economic activity [27][28][29][30][31]. Climate is considered a relevant variable that is correlated with COVID-19 [80,81], which increases the probability of risk of incidence and contagion [82] and indirectly affects economic activity.…”
Section: Plos Onementioning
confidence: 99%
“…The agriculture productivity primarily depends on climatic factors, namely, precipitation, temperature and evapotranspiration [3,4] . The precipitation (P), i.e., the quantity of rainfall, its intensity, and its distribution over an area during each cropping season can define the economy of any agriculture dependent country like India [5] . The precipitation and its pattern are also important for gaining an understanding of the micro-level availability of water, which in turn is useful for planning agricultural activities, and land and water development activities for future use [6] .…”
Section: Introductionmentioning
confidence: 99%